Gestão da relação volumoso: concentrado da dieta ao longo da terminação de novilhos confinados - Moura, Amanda Farias de (2017)
This study aimed to verify the effects of supplying different energy patterns on productive performance, ingestive behavior, and carcass characteristics of feedlot-finished cattle. Twenty-seven immunocastrated, pure and crossbred Charolais or Nellore animals with an initial average age and weight of 22 months and 252.8 kg, respectively, were used. Three treatments were carried out, two of them with an increasing rate of concentrate in the diet during the finishing period (TC5 and TC10) and one with constant roughage to concentrate ratio (TC). The experimental design was a completely randomized design with three treatments, five periods, and nine replications. The final weight was higher in TC (410.11 kg) and TC5 (408.72 kg) when compared to TC10 (397.17 kg). Average daily gain of steers had no difference between treatments and presented an average value of 1.453 kg day−1. Animals from CT presented a higher total weight gain (159.95 kg) when compared to TC5 and TC10. TC and TC5 presented the highest dry matter intake, both in absolute weight and in relation to live weight. No significant difference was observed in feed conversion, which presented a mean of 6.55 kg DM kg−1 LW. In the ingestive behavior, feeding time was higher for TC (4.31 hours) when compared to TC5 (3.85 hours). No significant difference was observed in rumination time and total leisure and standing. Steers from the treatment TC10 remained longer in lying leisure (8.14 hours) when compared to the treatment TC (7.24 hours). A superiority of chewing per ruminated bolus was observed in TC10 (58.59 seconds) when compared to TC5 (54.11 seconds) whereas a higher number of ruminated bolus was observed in TC5 (534.68 ruminated bolus day−1) when compared to TC10 (473.77 ruminated bolus day−1). Animals from TC presented a higher dry matter intake (9.54 kg day−1) than those from TC10 (8.63 kg day−1). Steers from TC and TC5 showed a higher NDF intake (3.63 and 3.58 kg day−1 for TC and TC5, respectively) when compared to TC10 (3.29 kg day−1). No significant difference was observed in slaughter and warm and cold carcass weights, as well as in carcass yield. Weight and yield of commercial cuts and metric carcass characteristics showed no significant differences. Weight loss during chilling was higher in carcasses of animals from the treatment TC10 (2.41 kg 100 kg−1 cold carcass) when compared to TC and TC5 (2.26 and 2.15 kg 100 kg−1 cold carcass, respectively). In the assessments of animal performance, the supply of a feeding pattern with a more marked change of concentrate in the diet results in steers with a lower final weight, total weight gain, and dry matter intake. However, animals submitted to a constant energy level showed a higher total weight gain. In the ingestive behavior, the supply of different energy patterns in the diet implies in changes of behavior and in activities inherent to rumination. Pattern supply with a more pronounced change causes a higher weight loss during carcass chilling.